PENGARUH FINANCIAL LITERACY, PENGETAHUAN LAPORAN KEUANGAN DAN PENDAPATAN TERHADAP PERILAKU PENGELOLAAN KEUANGAN PELAKU UMKM DI KECAMATAN MAUROLE KABUPATEN ENDE - Ferdinanda Camelia; Andreas Rengga; Katharina Yuneti (Jurnal Projemen UNIPA, 2025)
This study aims to examine the influence of financial literacy, financial reporting knowledge, and income on the financial management behavior of MSMEs in Maurole District, Ende Regency. This study uses a causal quantitative approach with an associative research type. This study used a sample of 75 MSMEs in Maurole District who met the specified criteria. The data used are primary data obtained directly from respondents, namely Micro, Small, and Medium Enterprises (MSMEs), through the distribution of questionnaires that have been compiled based on research variable indicators. The analytical method used includes multiple linear regression analysis. The results of the analysis show that financial literacy has a significant effect on financial management behavior. In addition, financial reporting knowledge has a significant effect on financial management behavior. And income also has a significant effect on financial management behavior. In addition, Financial Literacy (X1), Financial Reporting Knowledge (X2), and Income (X3) together have a significant influence simultaneously on the financial management behavior of MSMEs (Y). Therefore, increasing financial literacy and knowledge must be accompanied by a good income management strategy. This is crucial to separate business finances from personal finances and to ensure greater focus on supporting business sustainability.